Development of a disaster nursing training program for undergraduate interns in mobile cabin hospital settings - Shi, Lan; Liu, Min; Jian, Gang-Ren; Chen, Ji-Min; Li, Yan-Ran; Jin, Shuang (Frontiers in Public Health, 2025)
ObjectiveTo develop a structured “Disaster Nursing Practice Week” training program for undergraduate nursing interns, tailored to the context of mobile cabin hospitals, with the aim of enhancing disaster nursing competencies and providing a theoretical foundation for practical training.MethodsThe program was designed using the disaster management continuum theory in conjunction with the 2019 International Council of Nurses (ICN) updated Disaster Nursing Core Competencies framework. The Delphi method was employed to conduct two rounds of expert consultation, involving 15 professionals with expertise in nursing education, nursing management, disaster nursing, and emergency medicine.ResultsThe response rate for both Delphi rounds was 100%. The expert authority coefficient was calculated at 0.93. The coefficient of variation ranged from 0.000 to 0.205 in the first round and from 0.000 to 0.125 in the second round. Kendall’s coefficient of concordance (W) was 0.252 and 0.300, respectively (p < 0.001). The finalized training program comprised 8 primary indicators, 14 secondary indicators, and 47 tertiary indicators.ConclusionThe training program demonstrated a high degree of relevance and alignment with the practical needs of undergraduate nursing interns. It provides a systematic framework designed to enhance clinical competencies and strengthen disaster nursing preparedness within mobile cabin hospital environments.